Features of high-strength composite material structure creation - Semchenko, G. D.; Makarenko, V. V.; Logvinkov, S. M.; Shuteeva, I. Yu.; Katyukha, A. S. (Kluwer Academic/Plenum Publishers, USA, 2015)
The basis of technology proposed is use of a sol-gel method for preventing polycrystalline corundum fiber from crystallization during heating to high temperature and for low-temperature synthesis of prescribed phases in a corundum matrix with the aim of improving the operating properties of composite materials based on corundum. As a result of firing a charge based on corundum powder modified with tetraethoxysilane and polycrystalline corundum fiber modified with ethylsilicate-32 at 1360°C materials are created with very good strength properties. The materials exhibit electrical insulation properties and are stable in ionized gas streams at the level of known analogs as a result of creating self-reinforced mullite and β-SiC corundum matrix, reinforced with polycrystalline fiber and rapidly sintered due to presence of silicon oxynitride.
Keywords: mullite; modified fiber; tetraethoxysilane; silicon oxynitride